(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2014)
We report on a new method for preparation the magnetocaloric alloy Gd5Si4. By mechanical alloying under argonatmosphere and then melting sample by arc furnace, we produced the Gd5Si4 alloy. The structure and magnetothermalproperties of the alloy have been investigated with the help of powder X-ray diffraction and magnetization measurements.This compound crystallized in the orthorhombic structure with space group pnma. In X-ray powder diffraction pattern, aminor orthorhombic GdSi2 phase was observed as a second phase. For this compound, the second order phase transitionwas observed. The maximum isothermal magnetic entropy change of the Gd5Si4 compound at 348K was found to be -10J/(kg K) in an applied field of 0.5T.